Real-time imaging of lead nanoparticles in solution – determination of the growth mechanism. Issue 126 (10th December 2015) - Delach, Diana. L.; Dukes, Madeline J.; Varano, A. Cameron; Kelly, Deborah F.; Dukes III, Albert D.
Abstract : In situ electron microscopy is a tool which offers great promise for studying the mechanisms responsible for nanoparticle growth. Abstract : In situ electron microscopy is a tool which offers great promise for studying the mechanisms responsible for nanoparticle growth. In aqueous solution, the reduction of Pb 2+ by the electron beam results in the formation of lead nanoparticles. Here, we directly examined the fundamental processes that influence the growth of lead nanoparticles in solution using in situ transmission electron microscopy. Lead nanoparticle growth was directly monitored at the molecular level and followed the sequence of nucleation, Ostwald ripening, and aggregative growth. The aggregative growth phase resulted in macrostructures having micron-sized dimensions. Importantly, when combined with quantitative measurements, our direct imaging results suggested that the growth properties observed for lead nanoparticles were unique in comparison to other metallic entities.